Mitogen‐activated protein kinase inhibition‐induced modulation of epidermal growth factor receptor signaling in human head and neck squamous cell carcinoma. Issue 6 (3rd February 2021) - Xie, Guiqin; Zhu, Ailin; Gu, Xinbin
Abstract: Background: Epidermal growth factor receptor (EGFR) overexpression is one of the most notable characteristics in head and neck squamous cell carcinoma (HNSCC). The MAPK kinase (MEK) inhibitor trametinib has shown efficacy to treat HNSCC; however, the molecular mechanism remains unclear. Methods: HNSCC lines, mouse models, Western blot, and flow cytometry were employed to analyze the anticancer effects of trametinib. Results: The JHU‐011, JHU‐022, and JHU‐029 HNSCC cells with different genetic alterations were highly susceptible to trametinib. Trametinib effectively reduced EGFR expression, which was accompanied by the reduction of pro‐survival protein MYC, and the increased expression of a MYC‐targeted cyclin‐dependent kinase inhibitor p27kip1 and pro‐apoptotic protein BIM. Trametinib resulted in G1 arrest of the cells, markedly reduced cell numbers in S phase, and significantly increased apoptosis. In mouse models, trametinib strongly inhibited tumors growth. Conclusions: The MAPK–ERK signaling inhibition by trametinib may target EGFR and the downstream proteins against HNSCC.